Strategic Planning for the Management of Educational Institutions: Sistematic Review - Castillo, Mgs. Juan Alberto Castillo; Córdova, Mgs. Milquiades Enrique Roña; Orozco, Mgs. Evert Peña; Gurumendi, Johanna Maricela Bósquez (Journal of Ecohumanism, 2024)
This study aimed to analyze the trends and approaches of strategic planning in the management of educational institutions based on a systematic review of the literature of the last five years. Through a comprehensive analysis of 10 studies, the main challenges and opportunities in the implementation of strategic planning in the educational field were identified. The results of the review reveal the importance of strategic planning as a tool to improve educational quality, optimize resources and respond to the demands of an increasingly complex educational environment. However, recurring challenges are identified, such as lack of staff training, resistance to change and scarcity of resources. The active participation of the entire educational community, the adaptation of strategic plans to the particularities of each context and continuous evaluation are key elements for the success of strategic planning. Furthermore, the study highlights the need to strengthen transformational leadership and take advantage of the opportunities offered by information and communication technologies. In conclusion, strategic planning emerges as a fundamental tool to improve educational quality, but its effective implementation requires a comprehensive approach that considers the particularities of each context and the active participation of all the actors involved. Future research is recommended that delve into aspects such as evaluation, educational innovation and the impact of digital transformation on strategic planning.